2019
DOI: 10.15294/rainbow.v8i1.29756
|View full text |Cite
|
Sign up to set email alerts
|

Oscar Wilde's Writing Style in "The Happy Prince" in View of Transitivity Analysis

Abstract: This study was aimed to discover the types of processes used and how they influence the author’s writing style in Oscar Wilde’s short story entitled “The Happy Prince”. The methodology used in this study was descriptive-qualitative so the analysis was presented in the form of words, phrases, sentences, and utterances. The study focused on discourse analysis employing ideational function approach, which analyzed the short story from the point of view of linguistics especially Transitivity, a theory developed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Moreover, it is found that seven types of transitivity process in the short story provides different portrayal and reveal the context of the situation in the short story. As the result, the researchers found that Wilde's writing style consists of vivid descriptions, aesthetic appearance, conversational style, repetitive patterns, and simple and clear language (Sari & Yulianto, 2019). Moreover, it can be concluded that the employment of each process reveals different descriptions, thus the short story not only shows explicit content but also builds aesthetic values.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, it is found that seven types of transitivity process in the short story provides different portrayal and reveal the context of the situation in the short story. As the result, the researchers found that Wilde's writing style consists of vivid descriptions, aesthetic appearance, conversational style, repetitive patterns, and simple and clear language (Sari & Yulianto, 2019). Moreover, it can be concluded that the employment of each process reveals different descriptions, thus the short story not only shows explicit content but also builds aesthetic values.…”
Section: Introductionmentioning
confidence: 96%
“…The analysis of Oscar Wilde's The Happy Prince conducted by Sari & Yulianto (2019) proves that transitivity could reveal how each process type could influence the writing style of the author in developing the story. Moreover, it is found that seven types of transitivity process in the short story provides different portrayal and reveal the context of the situation in the short story.…”
Section: Introductionmentioning
confidence: 99%
“…Transitivity analysis has been also used for the literary texts. Sari and Yulianto (2019) analysed Oscar Wilde's Writing Style in" The Happy Prince" in View of Transitivity Analysis Afrianto and Seomantri (2014) conducted Transitivity analysis on Shakespeare's Sonnets. Haroon and Arslan (2021) applied Transitivity analysis of 'The Old Building'by Imdad Hussein by using corpus tool.…”
Section: Introductionmentioning
confidence: 99%